Corporate Purpose in the Era of Hashtag Capitalism: An Examination of New Zealand's Soon-to-be-Axed Amendment to the Directors' Duty of Care - Kamalnath, Akshaya (Victoria University of Wellington Law Review, 2025)
This article argues that in the era of 'hashtag capitalism', the Companies (Directors' Duties) Amendment Act 2023 might incentivise more online activism in New Zealand, which has not seen as much hashtag capitalism as in some other countries. The upshot of this is that society will be encouraged to engage with companies along specific guidelines. The article will also reflect on the proposal to repeal the amendment so soon after its introduction and argue that the expressive value of the amendment might remain, especially because the proposal to repeal the amendment did not provide much explanation for the repeal, and because the forces of hashtag capitalism will eventually diffuse into New Zealand. However, it will be important for New Zealand companies to learn from the experiences of jurisdictions like the United States where hashtag capitalism has been pronounced. Government and regulators must also be wary of the downsides of too much hashtag capitalism. In brief, these downsides include companies pandering to the loudest voices on social media and reacting quickly to these voices instead of careful consideration of issues in the interests of the company as a whole; people calling on companies to address social issues that are perhaps better addressed democratically; and as a corollary, companies rather than democratically elected leaders dictating the terms of important social issues.